SSTAF: Security Settings-Based Threat Assessment Framework of Programmable Logic Controllers - Meng, Jie; Zhang, Zhenyong; Zhu, Hengye; Yang, Zeyu; Deng, Ruilong; Cheng, Peng; Zhou, Jianying (IEEE transactions on information forensics and security, 2025)
Industrial control systems (ICSs) govern the production activities of various critical infrastructures, where programmable logic controllers (PLCs) are essential devices for controlling industrial processes. However, PLCs have many vulnerabilities and might be configured inappropriately. With the trend of PLCs connecting to the Internet, such weaknesses will lead to various cyberattacks and have prompted many studies on the threat assessment for PLCs. Previous research has ignored PLCs' security settings, such as operating mode and read/write authentication etc., which are the general security functionalities significantly affecting PLCs' security. In this paper, we make the first attempt to propose a security settings-based threat assessment framework (SSTAF) to assess PLCs' security. SSTAF consists of SScanner, a novel scanner to automatically extract the real-time configurations of security settings from PLCs, and the threat assessment criteria, serving to assess the appropriateness of PLC configurations and analyze risk levels of attacks based on PLCs' security settings. Subsequently, using SSTAF, we implement an Internet-wide threat assessment for PLCs exposed to the Internet. We deploy SScanner on the Internet and interact with 41K ICS devices in cyberspace to acquire their configurations of security settings. Based on the scanning result and the threat assessment criteria, we reveal that 93.32% of PLCs have not appropriately configured their security settings. Additionally, each PLC might be subject to 4.96 attacks on average, of which 3.32 attacks are due to the inappropriate configurations of security settings.